2017
DOI: 10.1161/jaha.117.006937
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Inappropriate Shocks and Other Health Outcomes Between Single‐ and Dual‐Chamber Implantable Cardioverter‐Defibrillators for Primary Prevention of Sudden Cardiac Death: Results From the Cardiovascular Research Network Longitudinal Study of Implantable Cardioverter‐Defibrillators

Abstract: BackgroundIn US clinical practice, many patients who undergo placement of an implantable cardioverter‐defibrillator (ICD) for primary prevention of sudden cardiac death receive dual‐chamber devices. The superiority of dual‐chamber over single‐chamber devices in reducing the risk of inappropriate ICD shocks in clinical practice has not been established. The objective of this study was to compare risk of adverse outcomes, including inappropriate shocks, between single‐ and dual‐chamber ICDs for primary preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…However, these potential benefits were not confirmed by randomized clinical trials. The benefits of reducing inappropriate therapy in dual chamber device is not very clear over single chamber device for primary and secondary prevention 28)29)30). Recent study reported that dual-chamber ICD showed an increased risk of periprocedural complications and generator replacement, whereas the risk of inappropriate shock is similar to the single-chamber ICD 31).…”
Section: Discussionmentioning
confidence: 99%
“…However, these potential benefits were not confirmed by randomized clinical trials. The benefits of reducing inappropriate therapy in dual chamber device is not very clear over single chamber device for primary and secondary prevention 28)29)30). Recent study reported that dual-chamber ICD showed an increased risk of periprocedural complications and generator replacement, whereas the risk of inappropriate shock is similar to the single-chamber ICD 31).…”
Section: Discussionmentioning
confidence: 99%
“…6 Varying data exist regarding the inappropriate shock rates of single-coil and dual-coil devices, though a number of studies suggest there is no significant difference between the two. [7][8][9][10] However, the other aforementioned factors support the thought posed by Gul et al, 1 that perhaps single-coil ICDs should be considered first for implantation before dual-coil devices wherever appropriate.…”
mentioning
confidence: 89%
“…16,17 In one large review, among patients who received an ICD for primary prevention without indications for pacing, dual-chamber devices were not associated with a lower risk of inappropriate shock or differences in hospitalization or death as compared with single-chamber devices. 18…”
Section: Device Selectionmentioning
confidence: 99%